Gender differences in the measurement of pharmacists’ job satisfaction - Carvajal, Manuel J. (Hum Resour Health, 2018)
BACKGROUND: Men and women choose different levels of commitment in their careers and at home. Compared to men, women value the significance of tasks performed and social relations more and earnings less. The objective of this study was to explore whether male and female pharmacists show the same levels of satisfaction overall and with key facets of their job, whether overall satisfaction is associated with satisfaction with 12 key facets of pharmacists’ jobs, and whether this association is similar for men and women. METHODS: The study used self-reported survey data collected from a random sample of licensed pharmacists practicing throughout the United States. The sample consisted of 436 males and 300 females. Pearson correlation coefficients were calculated to assess the association between overall job satisfaction and its key components. The 13 job satisfaction indices and the Pearson correlation coefficient values were compared by gender. RESULTS: Women were consistently more satisfied than men. Variations in overall job satisfaction were at best accompanied by moderate variations in the 12 job satisfaction facets, raising concerns about the validity of configuring a composite index from multiple indices of satisfaction. CONCLUSION: The results of this study can be used by healthcare managers and policymakers to facilitate communication, enhance teamwork, and promote a better allocation of scarce resources. Since men and women responded differently to various facets of their jobs, a constant set of rewards and stimulants may not be equally effective for both genders as employers transform the workplace to more adequately meet practitioners’ needs and increase their productivity. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12960-018-0297-5) contains supplementary material, which is available to authorized users.